HIGHER ORDER THINKING SKILLS (HOTS) DALAM PERSPEKTIF Q.S AN- NAHL AYAT 11 - Shofiah Mar’ah, Azmi; Moh. Sahlan (STAI Pelabuhan Ratu, 2024)
Higher Order Thinking Skills (HOTS) refer to cognitive abilities involving analysis, evaluation, and creation, which are essential in the learning process and problem-solving. In the Islamic context, the Qur'an invites believers to think critically and creatively, with over 300 verses encouraging higher-level thinking. A relevant verse, QS. An-Nahl (16:11), emphasizes the importance of reflection and understanding the signs of God's power. Through HOTS, individuals are expected not only to receive information but also to manage and apply it in daily life as a form of gratitude and practice of religious teachings. This article discusses the relevance of HOTS in developing human intellectual potential, the importance of cultivating a thinking culture in life, and the practical implications of sound understanding in producing righteous deeds. Emphasizing the use of reason as a trust highlights the distinction between humans and other beings, with the hope of achieving aspirations through constructive thinking.